Together in Pinecone Patch - Yezerski, Thomas F. (New York Farrar Straus, 1998)
A girl from Ireland and a boy from Poland overcome the prejudices held by the residents of the small American town to which they have emigrated.
Keywords: Prejudices -- Fiction; Immigrants -- Fiction; Love -- Fiction